Translocator protein (18 kDa) regulates the microglial phenotype in Parkinson's disease through P47. Issue 4 (1st April 2022) - Xue, Xue; Duan, Rui; Zheng, Guoyan; Chen, Hucheng; Zhang, Weiwei; Shi, Liang
ABSTRACT: Numerous studies have suggested that the phenotypic transformation of microglia plays a role in the pathogenesis of Parkinson's disease (PD). Translocator protein (TSPO) is an 18 kDa translocator membrane protein that acts as a marker of neuroinflammation and suppresses neuroinflammation; however, its underlying mechanism remains unclear. Although TSPO ligands were found to be protective in several neurodegenerative paradigms, few studies have evaluated their effects on microglial polarization, and underlying mechanisms need to be explored. In the present study, we examined the effects of TSPO and PK11195, a TSPO ligand, on lipopolysaccharide (LPS)+interferon (IFN)-γ-induced inflammatory factors and oxidative stress in microglia using enzyme-linked immunosorbent assay. The effect of TSPO and PK11195 on LPS+IFN-γ-induced microglial cell apoptosis was examined using immunofluorescence (IF), flow cytometry, and western blotting. The interaction between TSPO and P47 was investigated using IF and co-immunoprecipitation analysis. In vivo experiments confirmed the influence of TSPO and its ligand on motility, a-Syn, and dopaminergic neuronal damage. Our findings indicate that TSPO may regulate the microglial phenotype in PD via P47, suggesting a potential role in anti-PD therapy. Graphical abstract: uf0001